Comparison of the Wound Healing Activity of the Leaf and Leaf Ash Extracts of Vernonia amygdalina in Rats - Matovu, Isaac Joram; Bogere, Cissy; Othieno, James; Nakabiri, Winfred; Kahwa, Ivan; Ajayi, Clement Olusoji; Omara, Timothy; Iqbal, Shabnoor (Research square, 2023)
Background: Species in the genus Vernonia (Asteraceae) are traditionally used in the treatment of different ailments, for example, leaves in both fresh and dry forms have been used in dressing wounds. Anecdotal reports show that the ash of Vernonia amygdalina (V. amygdalina) has been used in the treatment of wounds, but there are no precise reports to support this claim; therefore, the contemporary study focused on comparing the wound healing activity of its leaf extracts and leaf ash. Methods: The study investigating the wound healing activity of V. amygdalina leaf was carried out in Wistar Albino rats in an excision wound model using its aqueous extract (AE) and leaf ash (LA) at concentrations of 1%, 2% and 3% (w/v). Mupirocin ointment and distilled water were used as positive and negative controls, respectively. The wound diameter was measured every 3 days from day 1 to day 22 and the results were used to calculate the percentage of wound reduction in all groups. Results: Significant wound healing activity was observed in all groups except 3% AE (w / v), against distilled water (negative control group) (p<0.05). Group 2 (1% AE), group 5 (1% LA), and group 6 (2% LA) showed faster wound healing than the positive control (p<0.05). Leaf ash was shown to have the best wound healing activity, and its lower concentrations worked better than the category of the same concentrations in aqueous extracts. Conclusions: Our findings have for the first time confirmed the traditional claim of using V. amygdalina ash in the treatment of topical wounds.
Keywords: Wound models; Traditional medicine; Uganda; Vernonia amygdalina